Gut Microbial Ecosystem in Parkinson Disease: New Clinicobiological Insights from Multi‐Omics - Tan, Ai Huey; Chong, Chun Wie; Lim, Shen‐Yang; Yap, Ivan Kok Seng; Teh, Cindy Shuan Ju; Loke, Mun Fai; Song, Sze‐Looi; Tan, Jiun Yan; Ang, Ban Hong; Tan, Yong Qi; Kho, Mee Teck; Bowman, Jeff; et al. (Annals of neurology, 2021)
Objective Gut microbiome alterations in Parkinson disease (PD) have been reported repeatedly, but their functional relevance remains unclear. Fecal metabolomics, which provide a functional readout of microbial activity, have scarcely been investigated. We investigated fecal microbiome and metabolome alterations in PD, and their clinical relevance. Methods Two hundred subjects (104 patients, 96 controls) underwent extensive clinical phenotyping. Stool samples were analyzed using 16S rRNA gene sequencing. Fecal metabolomics were performed using two platforms, nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography–mass spectrometry. Results Fecal microbiome and metabolome composition in PD was significantly different from controls, with the largest effect size seen in NMR‐based metabolome. Microbiome and NMR‐based metabolome compositional differences remained significant after comprehensive confounder analyses. Differentially abundant fecal metabolite features and predicted functional changes in PD versus controls included bioactive molecules with putative neuroprotective effects (eg, short chain fatty acids [SCFAs], ubiquinones, and salicylate) and other compounds increasingly implicated in neurodegeneration (eg, ceramides, sphingosine, and trimethylamine N‐oxide). In the PD group, cognitive impairment, low body mass index (BMI), frailty, constipation, and low physical activity were associated with fecal metabolome compositional differences. Notably, low SCFAs in PD were significantly associated with poorer cognition and low BMI. Lower butyrate levels correlated with worse postural instability–gait disorder scores. Interpretation Gut microbial function is altered in PD, characterized by differentially abundant metabolic features that provide important biological insights into gut–brain pathophysiology. Their clinical relevance further supports a role for microbial metabolites as potential targets for the development of new biomarkers and therapies in PD. ANN NEUROL 2021;89:546–559